Условия использования стеклообразных халькогенидных сплавов в дозиметрии высокоэнергетичных γ-квантов - Vakiv, N. M.; Golovchak, R. Ya.; Kovalsky, A. P.; Shpotyuk, O. I. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The specific features of using chalcogenide alloys of the nonstoichiometric ternary system (As2S3)x(Ge2S3)1-x in dosimetry of high-energy γ-radiation are analyzed. It is shown that when developing dosimetric systems based on these glasses, two essential factors must be taken into account: post-radiation relaxation of the monitored parameter and its temperature dependence in the radiation source channel.